KAJIAN KESEJAHTERAAN PETANI SAYUR DI KELURAHAN LINGKAR SELATAN KECAMATAN PAAL MERAH KOTA JAMBI - Mulyani Mulyani; James Rico Sinaga (Jurnal MeA (Media Agribisnis), 2022)
This study aimed to describe the income of farmers, the expenditure of farmers and assessing the farmers welfare in  Lingkar Selatan Village, PaalMerah District, Jambi City. The descriptive method was used in this research both qualitative and quantitative. The method used in data collection was a survey method. Sampling of 15% (40RTP) from the total farmers population (265 RTP) in a manner simple random sampling. Data analysis was performed with subsistence exchange rates (NTS). The result of this research showed that the average farmers income was Rp.18.524.250,-/year. Average farmers expenditure consists of farming expenses was Rp.24.608.476,-/year, while consumption expenditure was Rp.16.932/250,-/year. Farmers welfare in Lingkar Selatan Village, PaalMerah District, Jambi City had not been achieved yet as the NTS value was 0,44 (NTS<1).